Simple Future of Spanish. Natural System Versus Cultivated Uses - María Victoria Escandell-Vidal (Verba Hispanica, 2018)
The aim of this paper is to show that the attested diversity of interpretations of the Spanish simple future does not result from an inherent polysemy, but rather from the coexistence of two different systems being “visible” at the same time: an active, fully productive system (natural system), and a set of non-active uses, which survive from an ancient system no longer in force (cultivated uses). To this end, the paper examines data from first language acquisition patterns, frequency, distributional restrictions, range of usage, and interpretation routes. The distinction suggested is a crucial requirement for a monosemic approach to the semantics of the Spanish simple future cast in evidential terms – one that can make evident its internal logic and synchronic properties.